The influence of outdoor shoe sole stiffness on the metatarsophalangeal joint kinematics when walking and running in different conditions - Mistretta, P.; Parolini, G.; Marcolin, G.; Hasler, C.; Viel, L.; Petrone, N. (Proceedings, 2018)
Understanding the action of the metatarsophalangeal joint (MTP) is fundamental to improving the design process of a new outdoor shoe. Coming from the stated consideration, the aim of this research is to study the influence of shoe sole stiffness and terrain slope on the MTP joint angle of subjects walking in different conditions. To pursue this intent, different data collection sessions have been carried out in-vitro and in-vivo, indoor and outdoor. Two different approaches have been used to collect gait kinematics: an IMU (Inertial Measurement Unit) based system for the first campaign of tests, and a 2D video analysis for the second. Major findings showed a linear correlation between shoe sole stiffness and peak MTP joint angle during gait, as well as consistency in the value of the slope of the linear regression curves corresponding to the different conditions examined.